2006
DOI: 10.1073/pnas.0600865103
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific Abs against modified protein and DNA with oxidized lipids

Abstract: 4-Hydroxy-2-nonenal (HNE), a racemic mixture of 4R-and 4S-enantiomers, is a major product of lipid peroxidation and is believed to be largely responsible for the cytopathological effects observed during oxidative stress. HNE reacts with histidine to form a stable HNE-histidine Michael addition-type adduct possessing three chiral centers in the cyclic hemiacetal structure. We have previously raised the mAbs, anti-R mAb 310 and anti-S mAb S412, that enantioselectively recognized the R-HNE-histidine and R-HNEhist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…An anion exchanger (band 3) is a predominant autoantigen in erythrocyte membranes [39,40] and may correspond to the positive band observed at a high molecular mass in Figure 5(B). In addition, a lipid peroxidation product, 4-hydroxynonenal, and/or its protein adduct may be an antigen in oxidized erythrocytes [41].…”
Section: Discussionmentioning
confidence: 99%
“…An anion exchanger (band 3) is a predominant autoantigen in erythrocyte membranes [39,40] and may correspond to the positive band observed at a high molecular mass in Figure 5(B). In addition, a lipid peroxidation product, 4-hydroxynonenal, and/or its protein adduct may be an antigen in oxidized erythrocytes [41].…”
Section: Discussionmentioning
confidence: 99%
“…Another key feature of many autoimmune diseases is the presence of antinuclear antibodies. It is interesting to note, therefore, that antibodies against adducts of 4HNE, a carbonyl known to be elevated in COPD (13), have dual specificity against both DNA and 4HNE-modified protein leading to an antinuclear antibody-type response (39).…”
Section: Discussionmentioning
confidence: 99%
“…HNE exerts these effects because of its facile reactivity with biological materials, including proteins [2]. It is reported that the sequence of an anti-HNE monoclonal antibodies (mAb) has highly homologous to the anti-DNA autoantibodies [3]. Excess generation of reactive oxygen species (ROS) have the ability, either directly or indirectly, to damage proteins, DNA, lipids and other cell biomolecules [4,5].…”
Section: Introductionmentioning
confidence: 99%